Di Bawah Naungan Sang Kejora:"Nasionalisme" Papua Anti Indonesia? - I Ngurah Suryawan (PAX HUMANA, 2015)
This paper discusses the thought and imagination that exist among some Papuans about what they call "Papuan nationalism". One of the symbols of "nationalism" is the Bintang Kejora Flag. Papuan People construct their own social history which is always at odds with the effort to make the Papuans becomes Indonesian . The history of violence, suffering and discrimination of development in Papua had been planted into the soul of papuan people and that make different feelings such as anti Indonesia. This paper argues that the efforts of social movements for recognition of history and identity of the Papuan people has become very important. One of the effort that could be done is to bring the history back which is "darkened" on Papua through the motions of writing papuans own history among the Papuans themselves. Keywords: nationalism, history, violence, social movements, identity